2007
DOI: 10.1111/j.1440-1673.2007.01720.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery embolization for symptomatic fibroids with imaging follow up

Abstract: The aim of this study was to determine the effectiveness of uterine artery embolization (UAE) as a primary treatment method in treatment of symptomatic fibroids, whether there are any preembolization MRI characteristics of fibroid predictive of reduction in volume and assess reduction in uterine and dominant fibroid volumes using ultrasound (US) and MRI. Study was carried out in total of 32 patients aged 25-49 years (mean 40.9 years). Uterine and dominant fibroid volume were determined using US and MRI before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Two studies have demonstrated that T2 hyperintensity of leiomyomas correlated with higher volumetric response (6, 7). Our study, however, does not show a correlation between relative T2 signal intensity and volume response, similar to Jain et al (10). Discrepancy in our results may be related to differences in T2W imaging parameters (e.g., magnetic field strength, repetition time/echo time), the use of relative signal intensity ratios as opposed to subjective assessment of signal intensity, differences in composition of fibroids included in this study population and small sample sizes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Two studies have demonstrated that T2 hyperintensity of leiomyomas correlated with higher volumetric response (6, 7). Our study, however, does not show a correlation between relative T2 signal intensity and volume response, similar to Jain et al (10). Discrepancy in our results may be related to differences in T2W imaging parameters (e.g., magnetic field strength, repetition time/echo time), the use of relative signal intensity ratios as opposed to subjective assessment of signal intensity, differences in composition of fibroids included in this study population and small sample sizes.…”
Section: Discussionsupporting
confidence: 89%
“…Although, studies have shown that size and fibroid location may relate to volume reduction, thus far, no studies have demonstrated significant correlation between degree of enhancement and volume reduction (6, 7). Some studies have shown that high T2 signal correlated positively with volume reduction in a small number of patients but other studies have shown no such correlation T2 (6, 7, 10).…”
mentioning
confidence: 97%
“…Both studies enrolled patients with multiple fibroids; 18 patients with 32 leiomyomas and 11 patients with 45 leiomyomas, respectively. However, others reported no correlation between T2WI SI and leiomyoma volume reduction after UAE (19, 20). Most studies regarding fibroids and T2WI SI have included multiple myomas in each patient.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Some studies have tried to evaluate whether certain MRI characteristics relate to success, with many suggesting high T2-weighted signal intensity is associated with greater volume reduction or improvement of symptoms, 25,[32][33][34][35][36][37] although others have not found statistical significance. 24,38,39 High T1-weighted signal intensity has been proposed to be associated with lower volume reduction, 22,32 although it also has been found not to be associated with lower volume reduction. 26 Many studies report that enhancement is not necessarily associated with greater volume reduction, 24,25,32,39 although one has found significance.…”
Section: Atypical Growth Locationsmentioning
confidence: 99%